2014
DOI: 10.1111/ger.12161
|View full text |Cite
|
Sign up to set email alerts
|

A Persian version of Geriatric Oral Health Assessment Index

Abstract: The Persian version of the GOHAI can be used reliably to identify oral health-related concerns of older Persian speakers, but further research is needed to confirm its cultural consonance in this population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
11
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 24 publications
4
11
2
Order By: Relevance
“…However, the OHIP-14 is less sensitive to minor impairments of oral health-related quality of life than GOHAI (38). In the present study, the mean GOHAI-add score of iBMS patients was lower than scores previously observed in healthy populations of similar age (39)(40)(41). Moreover, 94.5% of iBMS patients had a lower self-perceived oral health-related quality of life.…”
Section: Psychological Statuscontrasting
confidence: 73%
“…However, the OHIP-14 is less sensitive to minor impairments of oral health-related quality of life than GOHAI (38). In the present study, the mean GOHAI-add score of iBMS patients was lower than scores previously observed in healthy populations of similar age (39)(40)(41). Moreover, 94.5% of iBMS patients had a lower self-perceived oral health-related quality of life.…”
Section: Psychological Statuscontrasting
confidence: 73%
“…The research places were health centers and family physicians' centers. The researcher interviewed each participant by a questionnaire, which included demographic data, cardiovascular risk factors (high blood pressure, diabetes, high blood fat, smoking, overweight, regular physical activity), number of taken medicine, artificial teeth, most recent dental check, Geriatric Oral Health Index (GOHAI), Geriatric Depression Scale (GDS), and Cognition Status Test (COST) validated for Persian culture (18)(19)(20)(21).…”
Section: Methodsmentioning
confidence: 99%
“…The GOHAI designed by Atchison (1990) to assess oral health was validated and has been reliable for Persian culture. Cronbach's alpha was 0.74 (20). The questionnaire has 12 questions regarding physical, psychological, and social domains.…”
Section: Methodsmentioning
confidence: 99%
“…Questions 3, 5, and 7 are scored in reverse. Minimum score is 12 points and maximum 60 points, and higher scores show a better status of oral health (11).…”
Section: Measurementmentioning
confidence: 99%